Childhood maltreatment increases the suicidal risk in Chinese schizophrenia patients - Cheng, Peng; Ju, Peijun; Xia, Qingrong; Chen, Yuanyuan; Li, Jingwei; Gao, Jianliang; Zhang, Loufeng; Yan, Fanfan; Cheng, Xialong; Pei, Wenzhi; Chen, Long; Zhu, Cuizhen; et al. (Frontiers in Psychiatry, 2022)
Objectives: Childhood trauma might be a modifiable risk factor among adults with serious mental illness. However, the correlation of child trauma and suicide is unclear, which were cited most frequently as the biggest challenge to schizophrenia patients in China. We aim to study relationships between child trauma and suicide in schizophrenia patients of different disease stages. Methods: Ninety-one participants were included and divided into two groups, namely, first-episode group (n = 46), relapsed group (n = 45). The Positive and Negative Syndrome Scale was used to evaluate the severity of psychotic symptoms. The Beck's Suicide Intent Scale and The Nurses’ Global Assessment of Suicide Risk were conducted by patient self-report to assess suicide symptom. The childhood trauma questionnaire was used to estimate severity of traumatic stress experienced during childhood. Results: Childhood trauma and different dimensions of suicide were significantly higher in the relapsed group than first-episode group (P<0.01, respectively). BMI has a significant positive relationship with recent psychosocial stress (β=0.473, t=3.521, P<0.001) in first-episode group. As in relapsed group, BMI has a positive effect between severe mental illness and suicide ideation (β=0.672, t=5.949, P<0.001; β=0.909, t=2.463, P<0.001), Furthermore, emotional neglect presented positively related to the suicide risk and proneness to suicidal behavior (β=0.618, t=5.518, P<0.001; β=0.809, t=5.356, P<0.001). Conclusion: Relapsed group of patients had significantly more severe childhood trauma, recent psychosocial stress, suicidal risk and proneness to suicidal behavior. BMI and emotional neglect are unique predictors for different dimensions of suicide.